Two-dimensional acoustic analysis using Taylor expansion-based boundary element method - Yang, Yan; Lei, Guang; Yang, Sen; Xu, Yanming (Frontiers in Physics, 2024)
The use of boundary elements in two-dimensional acoustic analysis is presented in this study, along with a detailed explanation of how to derive the final discrete equations from the fundamental fluctuation equations. In order to overcome the fictitious eigenfrequency problem that might arise during the examination of the external sound field, this work employs the Burton-Miller approach.Additionally, this work uses the Taylor expansion to extract the frequency-dependent component from the BEM function, which speeds up the computation and removes the frequency dependency of the system coefficient matrix. The effect of the radiated acoustic field generated by underwater structures' on thin-walled structures such as submarines and ships is inspected in this work.Numerical examples verify the accuracy of the proposed method and the efficiency improvement.